Associativismo e produção orgânica como uma alternativa para a agricultura familiar: o caso Aruatã - Vale, Arilson Pereira do (2003)
This work assumes as its central issue the reality of agriculture, and specially the familiar agriculture, in Brazil. The analysis of this thematic begins with the identification and characterization of the technological modernization model adopted in the Brazilian context. Therefore, it seeks to understand the conception of technology and technological development that based the political and economic options and to identify the rationality embedded in the process, since every social action brings a rationality of its own. In this itinerary of investigation are especially used the concepts of " instrumental reason" technological "appropriation" and "unappropriation" and even technology. The alternative practices of organic agriculture is presented as "technologically appropriated" in the context of familiar agriculture and oriented according to the principles of a communicative reason, as defined by Jürgen Habermas. Next the text tries to bring together the theoretical concepts and the proposition that associative and cooperative practices by familiar farmers are essentials for the construction of spaces where the communicative rationality really works and where the farmers can conquest their citizenship. The theoretical frame is finally confronted with a "case study" research about an association of organic farmers from Tijucas do Sul, named ARUATÃ. The objective is to analyze and realize the existent difficulties in the construction of an associative practice and the possible reasons that could explain why many associative initiatives, like Aruatã, don't prosper.